Motivation With Addition Dental At Lamkunyet Community Darul Kamal, Great Aceh District - keumala, cut ratna; Mardelita, Sisca (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2023)
Many people experience dental caries, but they delay treatment, such as dental fillings. The general public is not yet motivated to make dental caries fillings. Based on the results of the initial examination conducted by researchers from 15 people who have caries in the bad category 66.6% and 33.3% good category based on interviews, information was obtained from 15 people who have not patched because of fear of illness later. The purpose of this study was to determine the relationship between community motivation and dental fillings in Lamkunyet Village, Darul Kamal District. This type of research is analytic. The design used is cross sectional. Sampling by random sampling. The research location is Lamkunyet village. The number of respondents is 86 people. The results showed that intrinsic motivation p value = 0.00 (<0.05) means that there is a relationship between community intrinsic motivation regardi ng dental fillings. Extrinsic motivation p value = 0.048 (<0.05) means that there is a relationship between extrinsic motivation and dental fillings in Lamkunyet village, Darul Kamal District. It was concluded that there was a relationship between community intrinsic motivation and dental fillings in Lamkunyet village, Darul Kamal sub-district. There is a relationship between extrinsic motivation and dental fillings in Lamkunyet village, Darul Kamal Subdistrict, it is suggested to people who have never done or have done patches in order to increase their motivation to do carious dental fillings to sustain further damage.